SELECTION AND SUBSTANTIATION OF ENERGY-TECHNOLOGICAL SCHEME OF PLANT BIOMASS THERMOCHEMICAL CONVERSION - Воробйов, Леонід; Скляренко, Євген (Modern engineering and innovative technologies, 2022)
The article considers the prospects for the energy use of plant biomass and ways to improve the energy efficiency of its use. The choice and substantiation of the energy-technological scheme of the process of preliminary thermochemical conversion (process